2016
DOI: 10.1155/2016/9469276
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine as an Adjunctive Therapy for Breast Cancer: A Systematic Review and Meta‐Analysis

Abstract: Chinese herbal medicine (CHM) has been widely used as an adjunctive therapy for breast cancer, while its efficacy remains unexplored. The purpose of this study is to evaluate the efficacy of CHM combined with chemotherapy for breast cancer. The study results showed that CHM combined with chemotherapy significantly increased tumor response and KPS as compared to using chemotherapy alone (RR = 1.36; 95% CI = 1.24–1.48; P < 0.00001; RR = 1.38; 95% CI = 1.26–1.52; P < 0.00001, resp.). Besides, CHM as an adjunctive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…Traditional Chinese Medicine (TCM) has been widely used as an alternative therapy for breast cancer. Some TCM treatments can significantly improve the quality of life and overall survival of breast cancer patients [3][4][5]. TCM is related to the unity and integrity of the human body and its relationship with nature.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese Medicine (TCM) has been widely used as an alternative therapy for breast cancer. Some TCM treatments can significantly improve the quality of life and overall survival of breast cancer patients [3][4][5]. TCM is related to the unity and integrity of the human body and its relationship with nature.…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese herbal medicines have been regarded as promising adjuvant therapy for patients with BC. 8 Baicalin is a benzylisoquinoline alkaloid from Chinese herbal medicine Scutellaria lateriflora Georgi and its structure is exhibited as previous study, 9 which has been demonstrated to play anti-proliferation, anti-inflammatory and antimetastatic roles in human cancers or diseases. 4, More importantly, previous study suggests that baicalin could inhibit BC development in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the combination of modern western therapies and traditional Chinese medicine (TCM) is a common approach to treat breast cancer with bone metastases. As an important complementary therapy, Chinese herbal medicine can effectively resolve breast lumps, alleviate bone pain, minimize the adverse events of chemotherapy, and improve the overall health and well-being of cancer patients [4] .…”
Section: Introductionmentioning
confidence: 99%